Brain-stem serotonin transporter availability in maternal uniparental disomy and deletion Prader–Willi syndrome. (January 2018) - Krishnadas, Rajeev; Cooper, Sally-Ann; Nicol, Alice; Pimlott, Sally; Soni, Sarita; Holland, Anthony J; McArthur, Laura; Cavanagh, Jonathan
Summary: Prader–Willi syndrome (PWS) is a rare condition because of the deletion of paternal chromosomal material (del PWS), or a maternal uniparental disomy (mUPD PWS), at 15q11-13. Affective psychosis is more prevalent in mUPD PWS. We investigated the relationship between the two PWS genetic variants and brain-stem serotonin transporter (5-HTT) availability in adult humans. Mean brain-stem 5-HTT availability determined by [ 123 I]-beta-CIT single photon emission tomography was lower in eight adults with mUPD PWS compared with nine adults with del PWS (mean difference −0.93, t = −2.85, P = 0.014). Our findings confirm an association between PWS genotype and brain-stem 5-HTT availability, implicating a maternally expressed/paternally imprinted gene, that is likely to account for the difference in psychiatric phenotypes between the PWS variants. Declaration of interest: None.